Customer Loyalty in Purchasing Dietary Supplements Through E-Marketplaces in Central Thailand - Aiemchan, Hannarong; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2026)
This exploratory research examines external stimulus factors affecting customer loyalty in purchasing dietary supplements through E-Marketplace channels among customers in central Thailand. The study investigates obstacles and recommendations for customer loyalty in purchasing dietary supplements through E-Marketplace channels. Using purposive and quota sampling, data were collected from 100 respondents and analyzed through frequency distribution, percentages, means, standard deviations, One-Way ANOVA, Least Significant Difference comparisons, and Multiple Regression analysis. Results showed no significant differences in brand loyalty opinions among customers with different personal factors. However, external consumer stimulus factors, specifically user experience and price and promotion, significantly affect customer loyalty in dietary supplement purchases through E-Marketplace channels, serving as primary drivers influencing consumers’ repeat purchase decisions. User experience contributes to satisfaction and trust building, forming the crucial foundation for long-term business-customer relationships. The approaches that businesses should prioritize include building platform and store credibility, presenting transparent product information, and efficiently managing problems and complaints. Price and promotion play exceptionally important roles in attracting customers in highly competitive markets. Establishing appropriate pricing strategies and offering attractive promotions not only stimulate short-term sales but also serve as tools for long-term customer retention. To promote customer loyalty, businesses should integrate both approaches by enhancing user experience alongside presenting valuable prices and promotions, creating sustainable competitive advantages in the online dietary supplement market.
Keywords: And dietary supplements; Customer service; Payment convenience; Payment security; Platform trustworthiness; Price and promotion; Product quality; User experience